PERTANGGUNGJAWABAN NOTARIS DALAM PENYIMPANAN PROTOKOL NOTARIS DI PROVINSI KEPULAUAN RIAU: PERTANGGUNGJAWABAN NOTARIS DALAM PENYIMPANAN PROTOKOL NOTARIS DI PROVINSI KEPULAUAN RIAU - Agustianto, Agustianto (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Notary is a protocol for public officials who have a fairly large responsibility, namely to keep the notary properly because the notary is a document belonging to the state. However, in practice, notaries in the Riau Islands region face various obstacles in keeping the notary protocol. The purpose of this study is to analyze the notary's accountability to the protocol he has made. Based on the results of the study that there are obstacles for notaries in storing notary protocols, namely the lack of facilities in the form of adequate and adequate storage places. Then, there are no regulations governing the storage of notary protocols, the regulations used are regarding the notary code of ethics and the Law on Notary Positions. based on the Legal Responsibility Theory by Hans Kelsen, a notary who violates the law should receive sanctions as stipulated in the Ethics and Laws concerning the Position of a Notary. Therefore, the recommendation in this study is the need for special regulations regarding the storage of notary protocols.